The August Trials The Holocaust and Postwar Justice in Poland - Kornbluth, Andrew 1982- (Harvard University Press, 2021)
Andrew Kornbluth offers the first account of the August Trials, Poland's halting judicial reckoning with wartime collaboration. As evidence of popular participation in the Holocaust mounted, the government, judiciary, and citizenry turned the trials into a vehicle for salvaging a heroic vision of the past.